(untitled) (Comparative Professional Pedagogy, 2023)
The article is devoted to the study of problems related to teaching choreography in American schools. It is found that the long-term study of choreography in public and private schools played a secondary role or was positioned mainly as an extracurricular activity (within the scope of Art or Physical Education syllabi). It is noted that there is a certain inconsistency in the choreography education of American schoolchildren, which is caused by the low professional qualifications of teachers and their insufficient readiness to teach choreography at school. The directions of the educational policy of the American government regarding the improvement of school education standards, the content of curricula and educational programs, as well as the quality of choreography teacher training are analyzed. The content of school syllabi is studied and summarized in terms of highlighting the art of choreography as the main subject. It is established that a serious problem of teaching choreography in schools is the inconsistency of the content of syllabi and the unclear definition of the criteria for assessing the learning outcomes. It is found that American teachers take into account the fact that the introduction of dance choreography in schools contributes to the development of students’ creative thinking, leadership qualities, psychological comfort and health care. It is defined that issues regarding the development of higher education standards, certification of choreography teachers in each state, substantiation of requirements for obtaining a license, unification and standardization of terminology, legislation, improvement of state educational policy, as well as funding conditions, etc., remain debatable. It is concluded that choreographic education all over the world faces common problems: "Who should teach?", "Who should teach teachers and what should they teach?". The role of the modern choreography teacher is not only to teach dance steps, but rather to consciously manage the capabilities of the student with the help of dance teaching skills.